Conjuncture, confluence, configuration recounting the turning points in the narrative of former revolutionaries - Altobar, Elyn B. (The Mindanao Forum: official journal of the MSU-Iligan Institute of Technology, 2009)
This paper attempts to examine the question: what conditions inspire former members of the CPP-NPA in Mindanao to believe that the CPP-NPA-led revolution is the answer to the crisis in the Philippines. This paper is based on a recent study of the life history of former revolutionaries who are now settled or are working in the City of Tagum. That study describes the former revolutionaries' personal circumstances and their experiences in the family and community which stimulated the confluence of conditions inspiring the decision to join the revolutionary movement. This same confluence of conditions has some bearing on the nature of their subsequent experiences within the CPP-NPA, assuming forms impinged upon by certain events taking place in the nation's economy. In turn, these are explored for their significance in inducing conditions that had prompted their discontinuance from the movement. As well, the configuration of these factors are reviewed especially for the nature of adjustments they had to make in mainstream society after discontinuance from the movement. This configuration of conditions allows the former revolutionaries to observe how, even in the present, the incompatible, increasing, and broadening human aspirations of the peoples in the Philippines are unsatisfied by existing institutions. The past institutional failure to provide the means to address widening aspirations which causes revolutions to occur had degenerated in the present, intensifying the fervor of the movement. Essentially, the life history of the former revolutionaries is a function of the conjuncture of these conditions. Such conjuncture influences their perspectives about Philippine society and the revolutionary movement.